Al-Farabi's musical compositions Analytical study (Journal of the College of Basic Education, 2023)
It has become very necessary for us, exclusively Arab and ethnic music researchers.Standing on what was written by music scholars and its minstrels in the Abbasid period in which it wasMusic has reached advanced levels thanks to the studies made by philosophers.The well-known at the time, including Alfa Arbi, who is considered the second teacher after Aristotle.The researcher drew the attention of the proliferation of research centers and institutes of private music studies.Arab music in all capitals of the world, which is now working on studying and analyzing what they wrote.These philosophers of Arabic scales and rhythms, not to mention the printing of their musical manuscriptsknown.Most of the European orientalists, as we will notice in this research, have translated and studiedWhat Alfa Arbi and others wrote is like the nineteenth century, and so they continued in this vein.Now we have to work, study and analyze, especially since these works belong to us.More than others, it is our richest musical heritage on which Arab music theories are built.Since the days of these philosophers, and this is consistent and clear in their various manuscripts that are spread in libraries.and world capitals.Alpha Arbi is the name of a scholar and philosopher who lived in Baghdad and practiced playing and composing.A number of his musical compositions, which are the subject of research in the Turkish book Al-Azandeh, are:Samaei Ajam Mursa'i, in the honor of Ajam Marsa'i, Sama'i rests the souls.The book Al-Azandeh mentions that the ancient Turkish musicians wrote down these compositions by notes.Hadith, but it was not mentioned when this was done and by whom among the Turkish musicians.Alva Arbi's compositions are inscribed in modern notes, which we can analyze according to the musician's criterion.Bella Bartok Alhankari, who is internationally accredited, noting that the researcher has adapted the standard according toto the requirements of Arabic music, as there are points or aspects in the standard that may not applyArabic music in particular